Assessment of community based forest management practices in Benue State, Nigeria (2017)
Forests in Benue State are depleting due to anthropogenic activities. Community based forest management had been suggested by various researchers as being capable of stemming the rate of destruction of forests. This study was therefore carried out to assess the presence, mode and level of participation in community based forests practices in Benue State with a view to corroborate or dispute the veracity of the practice. Stratified multistage random sampling method was adopted to select 240 Household Heads who were later interviewed using 240 pre-tested semi-structured questionnaire. Data were analysed using descriptive and inferential statistics. Participatory Index analysis (PI) was employed to determine the extent of peoples’ involvement in various forestry practices. Likert scale rating was equally used to measure the factors motivating and inhibiting respondents’ participation in identified community forestry practices. Modal forestry practice identified was boundary planting (91.2%) with PI of 0.95, followed by home gardens (PI=0.93). Participation in physical execution of work (85.4%) was highest while only 15.8% of the respondents participated in decision making process. Most of the people who participated did so because the practices were relevant to their needs (WMS = 4.30>3.05) followed by the fact that they themselves were part of the planning process (WMS =3.90 > 3.05) while others said that level of literacy was not a hindrance to participation (WMS = 1.55 < 2.95). It was concluded that community based forest management practices existed in Benue State but participation in the practices was most in physical execution of work. It was recommended that people should be involved at the stage of planning, monitoring and evaluation to enhance better participation in Community Based Forest Management by the people.